Dynamics of Eco-Cities: A Review of Concepts towards Operationalizing Sustainable Urbanization - Amakpah, Steve-Wonder; Larbi, Martin; Liu, Gengyuan; Zhang, Lixiao (Journal of Environmental Accounting and Management, 2026)
The need for cities to transition towards a more sustainable urban development has become imperative given the combined impact of climate change, global ecological overshoot, and rapid urbanization. The Ecocity has emerged as an urban modernization concept that attempts to reframe urban development for sustainable outcomes, yet there have been several alterations and coining of new terminologies to describe an ecocity, mainly based of concepts and the design methodology and/or the purpose the city is to serve. Even though the eco-city concept and development profess to have some basic principles – dogma – mostly based on urban sustainability, the rapid changes in terminology in recent times calls the attention of many policy makers, investors, development promoters and stakeholders, as well as researchers alike. Beyond these corporate borders, are also the culture (people) and the environment that are influenced by (and interacts with) the eco-city. However, there is no widely accepted framework for assessing Eco-cities. Besides, the methods and outcomes of Eco-cities; and how these outcomes can be evaluated to determine the performance of Eco-cites remain unresolved. This paper presents a framework for assessing the performance of Eco-cities. It argues that due to the inherent differences in the culture, topography, climate, economy, infrastructural base, and technological advancement etc. of cities around the world, Eco-cities may embody distinct characteristics in the way they are understood and applied in different regions. Nonetheless, using a common benchmark across geographical regions, one can do performance assessment of Eco-cities, which can be basis for replication, accessibility, as well as serve as goal metrics.